Two different perspectives on heatwaves within the Lagrangian framework - A. Mayer; V. Wirth (Weather and Climate Dynamics)
Although heatwaves are one of the most dangerous types of weather-related hazards, their underlying mechanisms are not yet sufficiently understood. In particular, there is still no scientific consensus about the relative importance of the three key processes: horizontal temperature transport, subsidence accompanied by adiabatic heating, and diabatic heating. The current study quantifies these processes using an Eulerian method based on tracer advection, which allows one to extract Lagrangian information. For each grid point at any time, the method yields a decomposition of temperature anomalies into the aforementioned processes, complemented by the contribution of a pre-existing anomaly. Two different approaches for this decomposition are employed. The first approach is based on the full fields of the respective terms and has been established in prior research. In contrast, the second approach is based on the anomaly fields of the respective terms, i.e. deviations from their corresponding climatologies, and is introduced in this study. The two approaches offer two distinct perspectives on the same subject matter. By analysing two recent heatwaves, it is shown that the two decompositions yield substantial differences regarding the relative importance of the processes. A statistical analysis indicates that these differences are not coincidental but are characteristic of the respective regions. We conclude that the Lagrangian characterization of heatwaves is a matter of perspective.